Recent Progresses in Constructing the Highly Efficient Ni Based Catalysts With Advanced Low-Temperature Activity Toward CO2 Methanation - Lv, Chufei; Xu, Leilei; Chen, Mindong; Cui, Yan; Wen, Xueying; Li, Yaping; Wu, Cai-e; Yang, Bo; Miao, Zhichao; Hu, Xun; Shou, Qinghui (Frontiers in Chemistry, 2020)
With the development and prosperity of the global economy, the emission of carbon dioxide (CO2) has become an increasing concern. Its greenhouse effect will cause serious environmental problems, such as the global warming and climate change. Therefore, the worldwide scientists have devoted great efforts to control CO2 emissions through various strategies, such as capture, resource utilization, sequestration, etc. Among these, the catalytic conversion of CO2 to methane is considered as one of the most efficient routes for resource utilization of CO2 owing to the mild reaction conditions and simple reaction device. Pioneer thermodynamic studies have revealed that low reaction temperature is beneficial to the high catalytic activity and CH4 selectivity. However, the low temperature will be adverse to the enhancement of the reaction rate due to kinetic barrier for the activation of CO2. Therefore, the invention of highly efficient catalysts with promising low temperature activities toward CO2 methanation reaction is the key solution. The Ni based catalysts have been widely investigated as the catalysts toward CO2 methanation due to their low cost and excellent catalytic performances. However, the Ni based catalysts usually perform poor low-temperature activities and stabilities. Therefore, the development of highly efficient Ni based catalysts with excellent low-temperature catalytic performances has become the research focus as well as challenge in this field. Therefore, we summarized the recent research progresses of constructing highly efficient Ni based catalysts toward CO2 methanation in this review. Specifically, the strategies on how to enhance the catalytic performances of the Ni based catalysts have been carefully reviewed, which include various influencing factors, such as catalytic supports, catalytic auxiliaries and dopants, the fabrication methods, reaction conditions, etc. Finally, the future development trend of the Ni based catalysts is also prospected, which will be helpful to the design and fabrication of the Ni catalysts with high efficiency toward CO2 methanation process.